Maritime Boundary Management and Border Area to Increase Sovereignty Indonesian - Djalal, Hasjim (The Republic of Indonesia Defense University, 2015)
With the acceptation of UNCLOS 1982 by countries in the world, the Indonesia’s sovereign territories from the sea and the air have been increased ten times; hence, the Indonesian authorities on natural resources and other authorities have been widened dramatically. To use the widened and varied of natural resources, and to defend the unity of territories and the rights of Indonesian from the sea and the air, besides on the land, it needs a clear state’s boundaries on land and maritime border, seabed, and the air, and the increased ability of law enforcement and state’s defense that is widened and varied.